PENGGUNAAN KITOSAN DARI KULIT UDANG DALAM MENURUNKAN KADAR TOTAL SUSPENDED SOLID (TSS) PADA LIMBAH CAIR INDUSTRI PLYWOOD - Sampe Harahap (Berkala Perikanan Terubuk, 2010)
This research carried out in the laboratory of waste Processing Technologyand the laboratory of Water Quality Management in the FAPERIKA – UNRI. Theaim of this research is to identify the ability of chitosan in reducing the level ofTSS in the liquid waste of plywood industry. The method used in this research isexperimental study with complete randomized block, one factor, 4 level, 12 unitsof trial. Several chitosan concentration ie 0 mg/l, 15 mg/l, 30 mg/l appliedsampling were conducted in the is 8th hours, 12 th hours and 16 th hours.Resultshowh that 12 hours after addition of 30 mg chitosan / l, the quality of the wasteimproved : TSS 182,3 – 56,7 mg/l, Phenol 2,4 - 0,5 mg/l, BOD5 132-93 mg/l,COD 279-217 mg/l and pH 6 - 9. compared with KEP – 51/MENLH/10/1995 thequality of the treated waste is good so, it can be concluded that.